Effects of smail volum es of blood, isotonic and hypertonic saline administrotions on hoemodynomic porometers and blood goses in experimentolly induced hoemorrhagic sh.ock in dogs - Ercan Keskin; Mursayettin Eksen (Eurasian Journal of Veterinary Sciences)
In this study, the effects of smail volumes of blood, isotonic and hypertonic saline administrations in dogs with haemorrhagic shock induced experimentally were investigated. For thes purpose total/l 20 dogs were usedas a material. The dogs were divided info 4 groups each of 5 dogs. The dogs were anesthetized with thiopenthal sodium (30 mg/kg, iv), and then haemorrhagic shock was performed experimentally by taking arterial blood via cutdown catheter. By this way the mean arterial pressure (MAP) was reduced to 40±5 mmHg and maintained at this !eve! for 30 min. (Hypotensive period) by taking same mo re blood or reinfusion of the taken blood. At the end of the hypotensive period, the dogs of the group I,II,III and IV were treated by bolus injection of 5 ml/kg of blood, isotonic, 3.5 % and 7.5% NaCl, respectively. The blood samples for the determination of hemogram and blood gases analyses were taken before the experiment, at the and of the hypotensive period and after treatment at 30th, 60th mins and 90th mins and other paramaters were recorded. Before the experiment the MAP of the dogs in group I,II,III and IV were found to be 120.2, 114.2, 115.B and 132.4 mmHg respectively. This values were respectively found to be 40.4, 41.0, 41.0 and 43.6 mmHg at the end of the hypotensive period. After the bolus injection, the MAP at 90th min s. in group I,II, III and IV were determined to be 53.2, 52.2, 7 4. 6 and 100. B mmHg respectively. At the and of the hypotensive period, arterial pH in group I, III and IV decreased, whereas in group II it slightly increased. On the other hand, at the and of the hypotensive period, the aHC03 levels in the all groups decreased drastically when they were compared with the levels before the experiment.